Inheritances and gifts: Possibilities for a fair taxation of intergenerational capital transfers - Johannes Stößel; Julian Schneidereit; Sonja Stockburger (Intergenerational Justice Review)
In Germany, transfers of assets between generations are subject to inheritance and gift tax.1 However, there are different views on whether or not the present level of taxation is high enough. Our study looks at the potential for applying increases. We show that the constitutional framework does indeed allow for higher taxation in the case of intergenerational property transfers. We identify the essential points in current German inheritance and gift tax law, which make it possible to transfer large assets with no or low inheritance tax burden. For these points as well as the determination of tax rates, we propose reform approaches and present options for the use of possible additional income.